Performance of non-Saccharomyces yeasts isolated from Jiaozi in dough fermentation and steamed bread making. (August 2019) - Li, Zhijian; Li, Haifeng; Song, Kedan; Cui, Mingyu
Abstract: The characteristics of three non- Saccharomyces yeasts, namely, Wickerhamomyces anomalus Y13, Saccharomycopsis fibuligera Y18, and Torulaspora delbrueckii Y22, isolated from Jiaozi in dough fermentation and steamed bread making were investigated and compared with those of Saccharomyces cerevisiae Y10. The maltose levels in the dough fermented by Y13, Y18, and Y22 in the entire fermentation were higher than those in the dough fermented by Y10. The CO2 production kinetics of Y22 was similar to that of Y10, but the total CO2 volume was slightly less. The volume of CO2 produced by Y13 and Y18 was less than 30% of that generated by Y10. The sensory qualities of Y22-prepared steamed bread were similar to those of Y10 and could also be accepted. The degree of whiteness of the steamed bread prepared with Y22 was higher than that produced with Y10. Steamed bread produced with each of the non- Saccharomyces yeasts contained unique volatile compounds, and the highest number of categories of volatile compounds were observed in the product prepared with Y22. The results indicated that non- Saccharomyces yeasts exhibited distinctive characteristics of dough fermentation and showed the potential for applications in dough fermentation and steamed bread making. Highlights: Non-Saccharomyces yeasts in steamed bread production were evaluated. High maltose levels were detected in dough fermented by non-Saccharomyces yeasts. The CO2 production kinetics of T. delbrueckii Y22 and S. cerevisiae Y10 was similar. T. delbrueckii Y22 produced the highest number of categories of volatile compounds.